BIBLIOTECA ÎN CARE SE FACE, NU SE TACE - GHIURCO, președinte al Filialei Iași a Asociației Naționale a Bibliotecarilor și Bibliotecilor Publice din România, Bogdan (BIBLIOPOLIS, 2020)
The article is about the impressions after the workshop Explore. Create. Share – Makerspace and libraries – the example of the Köln Municipal Library. The Köln Municipal Library acts as a deeply democratic institution. It is a space of information, integration and inspiration, available to all, transforming the library in an indispensable space for the citizens. In recent years, the library has introduced many innovations, enjoying an increased attention among the public opinion. All the successes were able despite of the difficult financial situation, unfavorable spaces and personnel resources relatively small. On the librarians’ opinion, the budgetary problems are not priority when we are talking about future challenges, but it is important to have sustainable concepts.